Preeclampsia-Associated Alteration of DNA Methylation in Fetal Endothelial Progenitor Cells - Brodowski, Lars; Zindler, Tristan; von Hardenberg, Sandra; Schröder-Heurich, Bianca; von Kaisenberg, Constantin S.; Frieling, Helge; Hubel, Carl A.; Dörk, Thilo; von Versen-Höynck, Frauke (Frontiers in Cell and Developmental Biology, 2019)
Objective: The pregnancy complication preeclampsia (PE) represents an independent risk factor for cardiovascular disease. Our previous research shows a diminished function of fetal endothelial colony-forming cells (ECFC), a proliferative subgroup of endothelial progenitor cells (EPC) in PE. The aim of this study was to further investigate whether DNA methylation of fetal EPC is affected in PE. Methods: The genomic methylation pattern of fetal ECFC from uncomplicated and PE pregnancies was compared for 865918 CpG sites and genes were classified into gene networks. To explore whether expansion of fetal ECFC in cell culture leads to changes in global methylation status and if PE methylation characteristics are maintained with increasing passage low and advanced cell culture passages were compared. Results: A differential methylation pattern of fetal ECFC from PE compared to uncomplicated pregnancy was detected for a total of 1266 sites in passage 3, and for 2362 sites in passage 5. Key features of primary networks implicated by methylation differences included the cardiovascular system development and function, organizational development and cellular development. Cell culture passage 3 and 5 showed similar profiles of the gene networks. 1260 out of 1266 PE-associated methylation changes detected in passage 3 were confirmed in passage 5. Conclusion: Methylation modification caused by PE is stable and detectable even in higher cell culture passages. An epigenetically modified endothelial precursor may influence both normal morphogenesis and postnatal vascular repair capacity. To facilitate development of EPC based therapies for cardiovascular alterations further studies on epigenetic modifications in complicated pregnancies are needed.